The Role of Cooperative on the Socio-economic Growth and Stability - Kharel, Tika Ram (Journal of Durgalaxmi, 2024)
This study examines the role of cooperatives in fostering socio-economic growth and stability by addressing the collective economic and social needs of communities. Cooperatives serve as democratic and inclusive business models, contributing to community development, financial inclusion, and grassroots empowerment. Despite their substantial impact on rural development through resource mobilization and diverse financial support, cooperatives face challenges such as operational inefficiencies, limited technological integration, and governance issues. A set of structured questionnaires have been designed to obtain the information relating to various aspects of cooperative participation, economic benefits, and socio-economic impacts. Both closed-ended and open-ended types of questionnaires were formed to ensure depth and breadth of information. All the data were collected through 50 respondents using random sampling method and analyzed with descriptive statistical techniques. The study evaluates the current challenges and opportunities for cooperatives. The findings underscore their significant contributions to rural development and propose technology-driven strategies to enhance operational efficiency, governance, and adaptability to evolving member needs, ensuring their sustainable role in economic transformation.